Subspecialization in Family Medicine: Opinions, Preferences, and Practices of Family Physicians in Saudi Arabia - Mohammed A. AlAteeq; Abdullah S. AlJoudi; Yahia M. AlKhadli (SAGE Publishing, 2020)
Objective In recent years, family medicine (FM) has shown many changes, including the development of sub-specialization. This study aimed to explore the opinions, preferences, and practices of Saudi family physicians with regard to sub-specialization within family practice. Methods This cross-sectional study was conducted from January to May 2018. Data were collected from 561 Saudi FM board-certified physicians and family medicine residents from all over SA via personal emails using a self-administered questionnaire consisting of questions aimed at examining participants' opinions, preferences, and practices with regard to sub-specialization in family practice. Results Only 48 family doctors (20.2%) had the qualification of subspecialist. Diabetology was the most common clinical subspecialty. The majority of participants agreed with the statements in favor of sub-specialization in FM. About 73% approved of the idea of sub-specialization in FM, while 89% thought that sub-specialization would provide a source of expertise within the FM context. The most stated reasons to go for FM subspecialties were to earn more experience (65.1%), gain some sense of control of huge knowledge and skills of FM (53.7%), and earning extra money (47.8%). Conclusions This study revealed that majority of certified family physicians and FM residents in SA have positive attitude towards sub-specialization in FM and support the idea of sub-specialization to be practiced within the context of FM